Pelatihan Pemanfaatan Artificial Intelligence pada Guru Pendidikan Agama Islam (PAI) untuk Meningkatkan Efektivitas Pembelajaran di Kota Kediri - Anwar, Rosyida Nurul (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
In the era of globalization driven by the acceleration of advances in information technology, mastery and implementation of technology enable teachers to adapt and innovate in learning. Artificial intelligence in Islamic Religious Education (PAI) learning has great potential to increase the effectiveness and efficiency of the learning process. The purpose of implementing this community service is to provide an introduction and understanding to Islamic religious education teachers in learning the Islamic religion. The research stages were carried out in three phases: preparation, implementation and evaluation. The method for carrying out activities is through lectures, discussions, and direct practice using artificial intelligence. The activity participants were Islamic teachers at schools in Kediri City. The result of implementing the activity is that participants know the tools to learn Islamic religious education. Artificial intelligence allows teachers to develop skills in integrating artificial intelligence technology into learning, especially in Islamic religious education subjects.